Методы и модели автоматизированной диагностики технического состояния оборудования, планирования ремонтов и расчета коэффициентов готовности энергоблоков ТЭС и АЭС - Ефимов, Александр Вячеславович; Каверцев, Валерий Леонидович; Гаркуша, Татьяна Анатольевна (НТУ "ХПИ", 2010)
The methods and models of automated diagnostics of the technical state of equipment of heat and nuclear turbosets, prognosis of repair and calculation of efficiency are developed. The results can be proved in automated systems of control of technological processes for turbosets of heat and nuclear power plants.
Keywords: тепловая энергетика; атомная энергетика; энергоблок; ремонт оборудования; диагностика оборудования